2019
DOI: 10.1038/s41427-018-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

Bio-realistic synaptic characteristics in the cone-shaped ZnO memristive device

Abstract: We demonstrate inherent biorealistic synaptic plasticity functions in the Pt/n-ZnO/SiO 2-x /Pt heterostructures, where the n-ZnO semiconductor is geometrically cone-shaped in the size of a few nanometers. The synaptic functions were achieved within a two-terminal, electroforming-free, and low-power rectifying diode-like resistive switching device. The important rate-dependent synaptic functions, such as the nonlinear transient conduction behavior, short-and long-term plasticity, paired-pulse facilitation, spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 57 publications
(72 reference statements)
0
50
0
1
Order By: Relevance
“…Wang and coworkers [198] observed the learning experience-dependent plasticity in amorphous InGaZnO memristive devices. Sokolov et al [157] also observed a similar phenomenon in the cone-shaped ZnO memristive device, where the forgetting process was carried out by applying low-frequency stimuli. Then, the synaptic weight relaxes to an intermediate state during the forgetting process after removing the stimulus (see Figure 13a).…”
Section: Wwwadvelectronicmatdementioning
confidence: 68%
See 3 more Smart Citations
“…Wang and coworkers [198] observed the learning experience-dependent plasticity in amorphous InGaZnO memristive devices. Sokolov et al [157] also observed a similar phenomenon in the cone-shaped ZnO memristive device, where the forgetting process was carried out by applying low-frequency stimuli. Then, the synaptic weight relaxes to an intermediate state during the forgetting process after removing the stimulus (see Figure 13a).…”
Section: Wwwadvelectronicmatdementioning
confidence: 68%
“…www.advelectronicmat.de be utilized to mimic LTP with forgetting effect, [159,[161][162][163] STP to LTP transformation, [157,160,[164][165][166][167][168][169][170] metaplasticitry, [112,[171][172][173][174][175] and triplet-STDP. [176][177][178] The device structure, size, switching performance, and emulated synaptic plasticity of the representative memristive devices are summarized in Table 1.…”
Section: Memristive Synapsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various synaptic devices based on resistive switching, driven by different physical working mechanisms such as active metallic filament, charge trapping/detrapping effect, ions/vacancies migration, phase change behaviors, ferroelectric polarization, and spin‐transfer torque‐based synapses, have been demonstrated for emerging memory and neuromorphic computing. Many scientists are actively working to resolve various issues in those synaptic devices: high energy consumption, low switching speed, poor reliability, or the lack of high device density for integration.…”
Section: Introductionmentioning
confidence: 99%